Sex differences in the expression of lupus-associated miRNAs in splenocytes from lupus-prone NZB/W(F1) mice - Dai, Rujuan (BioMed Central, 2013)
BACKGROUND: A majority of autoimmune diseases, including systemic lupus erythematosus (SLE), occur predominantly in females. Recent studies have identified specific dysregulated microRNAs (miRNAs) in both human and murine lupus, implying an important contribution of these miRNAs to lupus pathogenesis. However, to date, there is no study that examined sex differences in miRNA expression in immune cells as a plausible basis for sex differences in autoimmune disease. This study addresses this aspect in NZB/W(F1) mice, a classical murine lupus model with marked female bias, and further investigates estrogen regulation of lupus-associated miRNAs. METHODS: The Taqman miRNA assay system was used to quantify the miRNA expression in splenocytes from male and female NZB/W(F1) mice at 17–18, 23, and 30 weeks (wks) of age. To evaluate potential estrogen's effect on lupus-associated miRNAs, 6-wk-old NZB/W(F1) male mice were orchidectomized and surgically implanted with empty (placebo) or estrogen implants for 4 and 26 wks, respectively. To assess the lupus status in the NZB/W(F1) mice, serum anti-dsDNA autoantibody levels, proteinuria, and renal histological changes were determined. RESULTS: The sex differences in the expression of lupus-associated miRNAs, including the miR-182-96-183 cluster, miR-155, miR-31, miR-148a, miR-127, and miR-379, were markedly evident after the onset of lupus, especially at 30 wks of age when female NZB/W(F1) mice manifested moderate to severe lupus when compared to their male counterparts. Our limited data also suggested that estrogen treatment increased the expression of aforementioned lupus-associated miRNAs, with the exception of miR-155, in orchidectomized male NZB/W(F1) mice to a similar level in age-matched intact female NZB/W(F1) mice. It is noteworthy that orchiectomy, itself, did not affect the expression of lupus-associated miRNAs. CONCLUSION: To our knowledge, this is the first study that demonstrated sex differences in the expression of lupus-associated miRNAs in splenocytes, especially in the context of autoimmunity. The increased expression of lupus-associated miRNA in female NZB/W(F1) mice and conceivably in estrogen-treated orchidectomized male NZB/W(F1) mice was associated with lupus manifestation. The notable increase of lupus-associated miRNAs in diseased, female NZB/W(F1) mice may be a result of both lupus manifestation and the female gender.